Iowa RBA, August 14-15, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for August 14-15, 1995. Highlights of the update include sightings of a second year Laughing Gull, an immature Yellow-crowned Night Heron, Red Knot, Piping Plover, fifteen American Avocets and an American Golden-Plover . Epson - sheet feed/flatbed